2018
DOI: 10.1038/s41467-018-07769-8
|View full text |Cite
|
Sign up to set email alerts
|

Murine hematopoietic stem cell activity is derived from pre-circulation embryos but not yolk sacs

Abstract: The embryonic site of definitive hematopoietic stem cell (dHSC) origination has been debated for decades. Although an intra-embryonic origin is well supported, the yolk sac (YS) contribution to adult hematopoiesis remains controversial. The same developmental origin makes it difficult to identify specific markers that discern between an intraembryonic versus YS-origin using a lineage trace approach. Additionally, the highly migratory nature of blood cells and the inability of pre-circulatory embryonic cells (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
4
11
0
Order By: Relevance
“…As a single HSC can expand vigorously from E10.5 onwards, it is possible that Lyve1 + cells in the AGM may have contributed to the total LT-HSC pool observed in these mice. Indeed, in a separate study, Lyve1 expression has been identified in the intra-embryonic P-Sp region prior to blood circulation (∼E8-E8.5) (Ganuza et al, 2018). In this study, intraembryonic Lyve1 + cells were capable of multi-lineage reconstitution in recipient mice after in vitro culture, providing further evidence that Lyve1 + cells in the P-Sp/AGM region contribute to the total fetal and adult LT-HSC pool (Ganuza et al, 2018).…”
Section: Fetal Lt-hsc Originsupporting
confidence: 60%
See 1 more Smart Citation
“…As a single HSC can expand vigorously from E10.5 onwards, it is possible that Lyve1 + cells in the AGM may have contributed to the total LT-HSC pool observed in these mice. Indeed, in a separate study, Lyve1 expression has been identified in the intra-embryonic P-Sp region prior to blood circulation (∼E8-E8.5) (Ganuza et al, 2018). In this study, intraembryonic Lyve1 + cells were capable of multi-lineage reconstitution in recipient mice after in vitro culture, providing further evidence that Lyve1 + cells in the P-Sp/AGM region contribute to the total fetal and adult LT-HSC pool (Ganuza et al, 2018).…”
Section: Fetal Lt-hsc Originsupporting
confidence: 60%
“…The idea that the first LT-HSC arises in the intra-embryonic AGM region is strongly supported by a collection of studies using in vitro and ex vivo tissue excision and cell transplantation assays, performed before or after the onset of blood circulation (North et al, 2002;de Bruijn et al, 2002;Medvinsky and Dzierzak, 1996;Muller et al, 1994;Kumaravelu et al, 2002;Gekas et al, 2005;Cumano et al, 1996;Boisset et al, 2010;Ganuza et al, 2018). Collectively, these studies demonstrate that LT-HSC activity can be identified as early as E10.5 from transplants of intra-embryonic P-Sp/AGM, but not yolk sac, tissues.…”
Section: Fetal Lt-hsc Originmentioning
confidence: 99%
“…Due to the immunophenotypic similarities between EMP and fetal HSC, the mechanism(s) that distinguish them functionally remains an open question. Genetic manipulations and prolonged in vitro culture from pre-circulatory concepti support the notion that yolk sac EMP develop from functionally distinct hemogenic endothelia compared to intraembryonic sources of HSC, suggesting a role for cell intrinsic programming (Chen et al, 2011; Ganuza et al, 2018). Both EMP and HSC express the transcription factor MYB, although it is only required for survival of HSC and not EMP (Mukouyama et al, 1999; Schulz et al, 2012; Sumner et al, 2000; Iturri et al, 2021).…”
Section: Introductionmentioning
confidence: 70%
“…To overcome these limitations, the Medvinsky laboratory developed an elegant culture system that allows for the ex vivo maturation of E8.5−E11.5 HSC precursors into transplantable HSCs [33][34][35][36]43,44]. Candidate HSC precursors sorted by fluorescence-activated cell sorting (FACS) from dissociated tissues and reaggregated with or without OP9 stromal cells have been reported to specify transplantable HSCs de novo using this system [27][28][29][30]37].…”
Section: Methodologies To Study Clonal Complexity During Embryogenesismentioning
confidence: 99%
“…In short, any system based on ex vivo culture suffers from unanswerable concerns regarding the preservation of native development. Thus, although this system is an excellent ex vivo surrogate from which many important biological insights have been derived [33][34][35][36]43,44], estimates regarding HSC precursor numbers and their dynamics are likely skewed. Thus, the need for systems to study unperturbed hematopoiesis.…”
Section: Methodologies To Study Clonal Complexity During Embryogenesismentioning
confidence: 99%